Pembinaan karakter nasionalisme melalui pembiasaan menyanyikan lagu kebangsaan pra pembelajaran di SMPN 2 Megaluh Kabupaten Jombang - Meylina Tria Ambarwati; Yuniastuti Yuniastuti; Desinta Dwi Rapita (Universitas Negeri Malang, 2021)
This study is based on the eroding sense of nationalism that is increasingly fading among the younger generation that makes the planting of nationalism values in the world of education is now beginning to be improved. This study aims to know the development of nationalism character, supporting factors, obstacles experienced, and how to overcome the obstacles experienced in the application of nationalism character building through habituation singing the pre-learning national anthem. This study uses qualitative approach with descriptive research type. The data sources used in this study are primary and secondary data sources. The data collection techniques in this study used non-participant observations, interviews, and documentation. Data analysis in this study was conducted by data collection. reduction of data, presentation of data, and withdrawal of conclusions. The implementation of singing the national anthem of Indonesia Raya to foster the character of nationalism in students at SMP Negeri 2 Megaluh is in accordance with Permendikbud No.21 Year 2015 on the Rules of The First Day of School Admission. The supporting factor in the development of nationalism character through habituation to sing the pre-learning national anthem at SMP Negeri 2 Megaluh is the existence of adequate facilities. The obstacles owned by SMP Negeri 2 Megaluh in carrying out the policy of singing the national anthem of Indonesia Raya to foster the character of nationalism in students are the lack of seriousness of students, speakers that do not function properly, and the lack of strict sanctions. The efforts that will be made in overcoming the obstacles of fostering the character of nationalism through habituation to sing the pre-learning national anthem at SMP Negeri 2 Megaluh are to reward, buy some new speakers, and give a reprimand to teachers who are less assertive. Kajian ini didasarkan atas terkikisnya rasa nasionalisme yang semakin lama semakin memudar dikalangan generasi muda yang membuat penanaman nilai-nilai nasionalisme dalam dunia pendidikan sekarang ini mulai ditingkatkan. Pendidikan karakter nasionalisme menjadi langkah efektif untuk membangun rasa semangat nasionalisme para generasi muda. Kajian ini bertujuan mengetahui pembinaan karakter nasionalisme, faktor pendukung, kendala yang dialami, dan cara mengatasi kendala yang dialami dalam penerapan pembinaan karakter nasionalisme melalui pembiasaan menyanyikan lagu kebangsaan pra pembelajaran. Kajian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Sumber data yang digunakan dalam kajian ini adalah sumber data primer dan sekunder. Teknik pengumpulan data pada kajian ini menggunakan observasi non partisipan, wawancara, dan dokumentasi. Analisis data dalam kajian ini dilakukan dengan pengumpulan data. reduksi data, penyajian data, dan penarikan kesimpulan. Pelaksanaan menyanyikan lagu kebangsaan Indonesia Raya untuk menumbuhkan karakter nasionalisme dalam diri peserta didik di SMP Negeri 2 Megaluh sudah sesuai dengan Permendikbud No.21 Tahun 2015 tentang Aturan Hari Pertama Masuk Sekolah. Faktor pendukung dalam pembinaan karakter nasionalisme melalui pembiasaan menyanyikan lagu kebangsaan pra pembelajaran di SMP Negeri 2 Megaluh adalah dengan adanya fasilitas yang sudah memadai. Kendala yang dimiliki oleh SMP Negeri 2 Megaluh dalam melaksanakan kebijakan menyanyikan lagu kebangsaan Indonesia Raya untuk menumbuhkan karakter nasionalisme dalam diri peserta didik adalah kurangnya kesungguhan siswa, speaker yang tidak berfungsi dengan baik, dan kurangnya sanksi tegas. Upaya yang akan dilakukan dalam mengatasi kendala pembinaan karakter nasionalisme melalui pembiasaan menyanyikan lagu kebangsaan pra pembelajaran di SMP Negeri 2 Megaluh adalah memberikan reward, membeli beberapa speaker baru, dan memberikan teguran kepada guru yang kurang tegas.